Exploring the physiological limits of aging: a case study of the male 50-km world record in the 80+ age category - Pilotto, A. M.; Higueras-Liébana, E.; Ansaldo, M.; Baltasar-Fernandez, I.; Neri, M.; Giusti, L.; Buendía-Romero, Á.; Valenzuela, P. L.; Alcazar, J.; Lauretani, F.; Re, R.; Botter, A.; et al. (Frontiers in Physiology, 2026)
Aging is associated with declines in cardiorespiratory fitness and endurance performance, but this association is usually confounded by age-related declines in physical activity levels. For this reason, world-class master athletes serve as exceptional models for elucidating the limits of endurance performance in old age.PurposeTo examine the physiological responses to exercise and performance characteristics of an 81-year-old male runner who, in 2025, set a new world record in the 50-km race (4h47m39s, 10.5 km h-1) in the 80+ category.MethodsTwo weeks after the world record, maximal O2 uptake (V˙O2max), fractional utilization of V˙O2max (lactate threshold [LT]), maximal fat oxidation (MFO) and running economy (RE) were assessed through incremental running tests. Limiting factors to V˙O2peak were assessed during incremental cycling exercise by gas exchange, peak cardiac output (Q̇peak), and peak fractional O2 extraction of the vastus lateralis (VL) muscle. In vivo VL muscle oxidative capacity and relative resistance to O2 diffusion were estimated using near-infrared spectroscopy (NIRS) during repeated transient arterial occlusions in well-oxygenated (kHIGH) and low O2 availability (kLOW) conditions.ResultsV˙O2max was 52.8 mL kg-1·min-1, achieved at 13.2 km h-1. LT was attained at 10.5 km h-1. MFO was 0.55 g·min-1 occurring at 84% of V˙O2max and RE was 237.5 mL kg-1·km-1. Cycling V˙O2peak was 2.510 L min-1 (42.6 mL kg-1·min-1), Q̇peak was 15.3 L min-1, and arterial-venous O2 difference was 16.4 mL dl-1, comparable to fractional O2 extraction around 75% obtained by NIRS. kHIGH was 4.67 min-1 and kLOW was 4.59 min-1, suggesting high oxidative and muscle O2 diffusing capacity.ConclusionThe exceptional endurance performance of this master athlete was attributed to his well-preserved V˙O2max (to our knowledge the highest recorded in octogenarians, equivalent to the 70th percentile for healthy males aged 20–30 years) and a high fractional utilization of V˙O2max, together with a great ability to oxidize fats. Analyses on the limiting factors to V˙O2max suggest that his exceptional performance was mostly due to the final steps of the oxygen cascade.